Tekanan Akademik Mahasiswa Akuntansi Berdasarkan Gender (Studi pada Mahasiswa Akuntansi UNUSIA) - Hudori, Hudri Ahmad; Fauziyyah, Nurul (Jurnal Pendidikan Akuntansi (JPAK), 2023)
This research aimed to provide a picture of the level of academic stress and the causes of the stress experienced by accounting students based on gender by analyzing and comparing the results of both to answer the question of whether there is a significant difference between the academic pressure experienced by male and female. This research used a survey method by distributing the instrument online through the google form. A total of 62 accounting students were chosen as the respondents in this study, including 27 male and 35 female students. The statistical analysis used in this research is the independent t-test using SPSS version 25 software. The results of this research showed that there was no significant difference between the academic stress experienced by accounting students, both male and female. This means that gender does not affect the academic stress experienced by accounting students at UNUSIA, however the average level of academic stress among accounting students is at a high category. Therefore, students and universities are expected to find ways to reduce the level of academic stress experienced. Students are able to cope with it by managing time and seeking social support and for universities it can be by providing counseling services for students.